2017
DOI: 10.48550/arxiv.1711.01358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strengthening Convex Relaxations of 0/1-Sets Using Boolean Formulas

Abstract: In convex integer programming, various procedures have been developed to strengthen convex relaxations of sets of integer points. On the one hand, there exist several general-purpose methods that strengthen relaxations without specific knowledge of the set S of feasible integer points, such as popular linear programming or semi-definite programming hierarchies. On the other hand, various methods have been designed for obtaining strengthened relaxations for very specific sets S that arise in combinatorial optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…since w i + w 1 ≥ 1 for all i = 1, so one has w i ≥ 1 − w 1 > 1/2. Thus, we can assume that (7) has the form (9). Note that inequality…”
Section: T |mentioning
confidence: 99%
See 1 more Smart Citation
“…since w i + w 1 ≥ 1 for all i = 1, so one has w i ≥ 1 − w 1 > 1/2. Thus, we can assume that (7) has the form (9). Note that inequality…”
Section: T |mentioning
confidence: 99%
“…It is an open problem whether an extended relaxation with this properties exists. Recent results showed the existence [1] and gave an explicit construction [7] of a linear relaxation for MinKnap of quasi-polynomial size with integrality gap 2 + ǫ. This is obtained by giving an approximate formulation for Knapsack Cover inequalities (KC) (see [4] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to observe that there is indeed a gap between the existence of certain extended formulations, and the fact that we can construct them efficiently: for instance in [5], it is shown that there is a small extended formulation for the stable set polytope that is O( √ n)-approximated (with n being the number of nodes of the graph), but we do not expect to obtain it efficiently because of known hardness results [18]. In another case, a proof of the existence of a subexponential formulation with integrality gap 2 + ǫ for min-knapsack [4] predated the efficient construction of a formulation with these properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…We now use the term notch to avoid confusion with the definition of pitch due to Bienstock & Zuckerberg [1]. The difference between pitch and notch is discussed in [11].…”
Section: Introductionmentioning
confidence: 99%